As estratégias da Academia Acqua Fitness e seu impacto no comportamento de seus consumidores - Glória, Rafaela Sicsú da (Brasil, 2022)
Nowadays the market is increasingly globalized and consequently more competitive. Due to the great access to information, consumers have become much more demanding about what they want to consume. In this way, it is up to companies to constantly seek to devise strategies to stand out from their competitors and gain the preference of their consumers so that they survive in the market. One of these strategies that has stood out is the study of consumer behavior, which according to Ferreira and Carvalho (2010) is a decisive aspect for companies to achieve their organizational goals. Within this study, the search for identifying the main factors that can influence the purchase decisions of consumers out, which are cultural, social, personal and psychological factors (ROCHA and IGNACIO, 2017; KOTLER and ARMSTRONG, 2000). Thus, given the importance of this theme, this research sought to understand the main factors that influence the purchase decisions of consumers at Academia Acqua Fitness in Parintins/AM. As for the methodological procedures, qualitative research with a descriptive design was used as an approach. In the descriptive research, the case study method was used. For data collection, an online form, semi-structured interview, in loco observation and document analysis were used as instruments. Finally, for data analysis, content analysis was used. As a result of the research, it can be seen that the factors that most influence the consumption decision of Acqua Fitness gym customers are personal factors and psychological factors.